Study on the National Conditions of Modernization with Chinese Characteristics - Hu, Angang; Zhou, Shaojie; Xie, Yize.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This is an open access book. Based on the analysis of China$1 (Bs basic national conditions and development trends, this book begins with a general introduction to the study of (3z(Bmodernization with Chinese characteristics,(3y (Band then discusses the comprehensive construction of a prosperous society in all respects, unprecedented changes, the new national system, green modernization, and technological modernization. In addition, there will be a presentation of in-depth research on topics such as leapfrog development of human capital market, the new stage of socialism, common prosperity in 2035 and a summary of the basic characteristics and great significance of modernization of a Chinese-style economy, technology, and education. Through historical comparison, this work will show the development, stages and future prospects of modernization with Chinese characteristics -- focusing on international comparison, especially a quantitative comparison with Western countries. This will further highlight the fast-paced effect of modernization with Chinese characteristics, and place emphasis on the uniqueness and innovativeness of modernization with Chinese characteristics.s
Analysis of the Characteristics and Significance of Chinese-style Modernization Road -- How China can build a moderately prosperous society in a comprehensive way: System Evaluation and Important Implications -- Year of Finishing Moderately Prosperous Society Construction in All Respects in 2020: Evaluation of China$1 (Bs Economic and Social Development -- China and the World Have Undergone Major Changes Unseen in a Century: Basic Trends and Future Trends -- A New National System: Background, Basic Features and Applicable Fields.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Economics; Political planning; Political Economy and Economic Systems; Public Policy